Formal methods applied to complex systems: implementation of the B method - Boulanger, Jean-Louis (Computer engineering series, 2014)
This book presents real-world examples of formal techniques in an industrial context. It covers formal methods such as SCADE and/or the B Method, in various fields such as railways, aeronautics, and the automotive industry. The purpose of this book is to present a summary of experience on the use of "formal methods" (based on formal techniques such as proof, abstract interpretation and model-checking) in industrial examples of complex systems, based on the experience of people currently involved in the creation and assessment of safety critical system software. The involvement of people from within the industry allows the authors to avoid the usual confidentiality problems which can arise and thus enables them to supply new useful information (photos, architecture plans, real examples, etc.). The authors cover the following topics: an example of use of SCADE, constraint solving in B, validation of Petri Nets-based automated rail safety, data validation, etc.